Statistical Analysis of Trends of Foreign Economic Activity of Ukraine: ICT Sector - Oleksiy Korepanov (Соціальна економіка, 2018)
The article is devoted to the statistical analysis of the trends of foreign economic activity of Ukraine, in particular, the ICT sector. The study identifies and analyzes the most complete and reliable source of world trade statistics – the database of UN Comtrade Database, on the basis of which the foreign trade of the most developed countries of the world and Ukraine in the groups of products and services of the ICT sector is investigated. According to the results of the study, the main changes of the data elements and functions of the UN Comtrade Database have been identified and described. The analysis of the state of the information society was started from the formation of the information base of the Ukrainian trade in services of the ICT services on the basis of Extended Balance of Payments Services (EBOPS), which are related to the specified sector. The collected data analyzed the trade balance of Ukraine in the main types of ICT services exported from Ukraine and imported into Ukraine, as well as the dynamics of export and import of ICT services in Ukraine for 2000-2017, and the corresponding diagrams for visual analysis were constructed. Using the UN Comtrade Database, the annual data on the cost of foreign trade in goods of ICT in Ukraine in 2010-2017 by the codes of the HS 2012 Harmonized Goods Description and Coding System and EBIT 2002 services by ICT were obtained and analyzed. According to the results of the survey, it was found that during the entire period under investigation the trend of increasing the volumes of both export and import of ICT products was noted, although in both cases this tendency was not stable. The negative factors influencing on the development of foreign trade in goods and services of ICT were: unfavorable conditions of external risks for domestic producers, insufficient level of competitiveness of their products, low activity of regions in the foreign market, imperfection of the commodity structure of expo rts and imports. In further research for the main components of export and import of ICT products, it is expedient to analyze monthly information and build appropriate forecasts.